1930
DOI: 10.1002/zaac.19301900113
|View full text |Cite
|
Sign up to set email alerts
|

Über die Sulfide der seltenen Erden

Abstract: Es wurden die Disulfide von Lathan und Cer, sowie die Sesqui‐ sulfide von Scandium, Yttrium, Lanthan, Cer, Praseodym, Neodym, Samarium, Gadolinium, Dysprosium, Erbium und Ytterbium dargestellt, eine Reihe davon erstmalig. Die erhaltenen Präparate wurden durch Röntgendiagramme, Farbbestimmungen, Dichtemessungen und Bestimmung des Magnetismus charakterisiert.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
1

Year Published

1931
1931
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(13 citation statements)
references
References 10 publications
1
11
0
1
Order By: Relevance
“…Hauser indicated that the zirconium and thorium oxysulfides were pyrophoric. Without knowing it, Klemm et al were probably the first to obtain a pure phase of Ln 2 O 2 S by heating Er(SO 4 ) 3 in H 2 S and consequently getting Er 2 O 2 S, that they only described as pale pink and resistant to other heating treatments in H 2 S (Klemm et al, 1930).…”
Section: Discovery and First Phasesmentioning
confidence: 99%
“…Hauser indicated that the zirconium and thorium oxysulfides were pyrophoric. Without knowing it, Klemm et al were probably the first to obtain a pure phase of Ln 2 O 2 S by heating Er(SO 4 ) 3 in H 2 S and consequently getting Er 2 O 2 S, that they only described as pale pink and resistant to other heating treatments in H 2 S (Klemm et al, 1930).…”
Section: Discovery and First Phasesmentioning
confidence: 99%
“…(3) where YY and Ss denote the yttrium atom and the sulfur atom at its lattice point, respectively, and e' denotes the conduction electron. When n is the density of conduction electrons, the equilibrium constant for reaction (3) can be written as (4) According to the electrical neutrality condition, 3[Yi]=n, we have…”
Section: Dependence Of Electrical Conductivity On Sulfur Partial Presmentioning
confidence: 99%
“…In this group Sc has the shortest bond length to S, and Sc2S3 is one of the structure types. Its study commenced over fifty years ago when it was prepared by the action of H2S on ScC13 (Klemm, Meisel &von Vogel, 1930). Attempts then made to deduce its structure from X-ray powder diffraction analysis were unsuccessful.…”
Section: Introductionmentioning
confidence: 99%